Development of Mathematics Learning Activities Using Mathcitymap at Sindu Kusuma Edupark to Learn Contextual Problem-Solving - Tyas, Azkia Martiana Winarning; Herningtyas Ayu Putri Cahyanti, Aurelia; Rudhito, Marcellinus Andy (Jurnal Pendidikan Matematika (JPM), 2024)
Contextual problem-solving abilities are very much needed in processes in the 21st-century era and can be done by providing meaningful experiences. This can also be called Outdoor Learning, namely involving students directly in the learning object. One application that can help learning outside the classroom is MathCityMap. This research raises the context of using ethnomathematics-based MathCityMap located at Sindu Kusuma Edupark. Sindu Kusuma Edupark is an educational tourist attraction located in Sleman, Yogyakarta. This research aims to develop students' contextual problem-solving abilities in mathematics learning using the MathCityMap application at the junior high school level. This research uses a type of development research called Research and Development (R&D). The method in this research refers to the 4D method which consists of 4 stages: definition, design, development, and dissemination. The results of this research are a series of learning activities using the MathCityMap application in the context of the Sindu Kusuma Edupark tourist attraction which colleagues have tested. The average assessment result is 80.5% with the feasible category. Based on these results, it was concluded that the MathCityMap activity developed by this researcher could be implemented in mathematics learning.